Non-Linear Analytical Model for Bread-Loaf Linear PM Motor - Turun, Ferhat; Sapmaz, Tunahan; Oner, Yasemin; Ali, Salman; Marignetti, Fabrizio (MDPI, 2025)
This article presents a non-linear MEC for a linear PM motor, and its experimental validation. In the MEC model, winding flux leakage and iron saturation are considered. In addition, two different linear PM motor models (bread-loaf and surface-type) are examined for linear PM motors. An iterative method is used to predict the magnetic behavior of saturated magnetic steel. The proposed MEC for linear PM motors is compared with finite element analysis (FEA) to determine its accuracy and suitability. FEA is widely regarded as a highly accurate and reliable tool for analyzing linear PM motors. However, its primary limitation lies in its considerable computational time requirement. This disadvantage becomes particularly problematic during the early stages of the design process. Therefore, the proposed model addresses this limitation. Also, experimental results validate the practicality of the MEC. Finally, the proposed model can be a tool for different slot/pole combinations. Thus, the model can be considered suitable for both bread-loaf and surface-type PM motors.
Keywords: analytical model; magnetic equivalent circuit; linear PM motor; bread-loaf; MAGNETIC-FIELD; MACHINES; OPTIMIZATION; PERFORMANCE; INSET; Energy & Fuels